Carbon emission reduction effects of digital infrastructure construction development: the broadband China strategy as a quasi-natural experiment - Ren, Huiming; Zhou, Jiawen; Yu, Yunjiang; Ye, Mingque (Frontiers in Environmental Science, 2025)
Research on carbon emission reduction in China has focused on carbon market policies, technological innovation, and industrial institutional adjustment, but few studies have been concerned with the effects of the rapid development of China’s digital economy on carbon emission reduction. China’s vigorous development of digital infrastructure has led to the establishment of the Broadband China strategy as a quasi-natural experiment. A difference-in-differences model with data from 2006 to 2023 about 283 prefecture-level cities was applied to investigate the effects of China’s digital infrastructure construction on carbon emission reduction. The conclusions are as follows. First, digital infrastructure construction in these cities had significant reduction effects on carbon emissions and intensity. This conclusion was proven after a series of robustness tests such as parallel trends, the exclusion of central cities, and the replacement of explanatory variables. Second, a mediating effect test showed that green technology innovation investment and industrial structure upgrading are important mechanisms for digital infrastructure construction’s carbon emission reduction effects. Third, these effects have obvious heterogeneity and are stronger in the eastern region than in the central and western ones. Moreover, the effects are stronger with the expansion of urban scale, the improvement of urban economic development level, and the environmental regulation intensity. These conclusions have important relevance to China’s Digital Economy and “Dual Carbon” Policies.